Predisposing factors and associated symptomatology of British soldiers requiring a mental health assessment. Issue 2 (1st June 2010) - Finnegan, Alan; Finnegan, S; Jackson, C; Simpson, R; Ashford, R
Abstract : Objectives: To critically evaluate the predisposing factors and symptomatology that resulted in serving officers and soldiers requiring a Mental Health (MH) assessment. Methods: 317 regular Army personnel who required a formal MH assessment completed a survey that detailed the predisposing factors and symptoms leading to the referral. SPSSv10 was used for data management and analysis of the data by descriptive and inferential statistical methods. Results: Three quarter presented with at least two predisposing factors, the commonest being family issues (42%), relationship problems (40%) and general military stress (39%). Up to half of young male Soldiers required a MH assessment as a result of wanting to leave the Army, and were positively associated with self harming ideology. Female soldiers are significantly over represented. No-one reported feeling isolated. Conclusion: The majority of personnel accessing the Army MH Services present with multi-factorial problems and symptoms that should result in colleagues being aware of their distress, and every effort must be made to support these soldiers within unit lines. That no one reported feeling isolated, challenges the perception that soldiers with MH problems are stigmatised. In those young male soldiers who wish to leave the Army there are indicators that significant periods of notice to leave can have a negative impact on MH. It is unclear why females are more likely to require support. If the emerging themes noted in this study are addressed, and the lessons learnt encapsulated within a predictive theoretical model, then the result could be an improvement in operational capability through the early return of Army personnel and Officers to full duty.